(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim purpose of research is to study the impact of the war in Syria on working women, by surveying the point of view of a number’s working women in government sector in Damascus and the countryside of Damascus, about the most important economic and social problems that they suffer from even new conditions they did not live with and their society had never before. In order to achieve the goal of the research, the researcher prepared a form that was applied to a sample of female workers attending community development centers in the city of Damascus and its countryside during the period between 1/12/2020 and 12/27/2020, the sample size was (100) working women, the form included the characteristics of the sample members. And their perceptions about the impact of war on women work by monitoring the economic and social problems they face and the causes of these problems, leading to their proposals to limit the negative effects of war. The most important research results: • All members of the research sample agreed on the existence of an impact from the social and economic aspects of war on working women. • The deterioration of living conditions is one of the most important causes of the problems faced by the working woman, according to the answers of the members of the research sample. • The difficulty of raising children and the presence of undesirable behaviors are among the most important social problems that the working woman suffers from, according to the answers of the research sample. • The cost of living and the increase in expenses are among the most important economic problems that the working woman suffers from, according to the answers of the research sample.